Interjections and L2 learning and teaching - Petrova, Krasimira (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2020)
INTERJECTIONS have been underestimated words in linguistics, and even more in linguodidactics. In recent years, interest in describing interjections has grown. The pragmatic approach is the most successful in their description. A comparative study of interjections and onomatopoeia in the Russian and Bulgarian languages has been carried out. Various theoretical frameworks and perspectives for describing interjections and onomatopoeias are proposed, but in this article they serve the goals of linguodidactics, teaching and learning a foreign language – L2. In our opinion, there is a need to study interjections at all stages of studying / teaching - from elementary to advanced, for greater expressiveness, communicative adequacy. Using so called “small words” in a suitable situation and context, we compensate for the lack of vocabulary and maintain communication, express our attitude to what is being reported. Interjections are associated with the mastery of speech etiquette as well, with the borrowing- internationalisms. Interjections are used in the comics, jokes, cartoons, videos; they are related to the emoticons, emoji. They are included in the lexicon, grammar; with suitable intonation and nonverbal behavior they are a part of L2 linguistic, socio-cultural, strategic, discourse competence. Interjections are also pragmatic and discoursive markers, serving for successful communication, or may be a marker for code-switching in bilinguals.